Cross-cultural adaptation and psychometric evaluation of the child oral health impact profile-short form 19 (COHIP-SF 19) for Ethiopian schoolchildren - Yilkal Tafere; Achenef Asmamaw Muche; Amare Tariku; Alemnew Athirsaw; Kassahun Alemu (BMC Oral Health)
Abstract Background Poor oral health can cause pain, discomfort, and reduced oral health-related quality of life (OHRQoL) affecting children’s social interactions, self-esteem, and school participation. Understanding OHRQoL and its impact is essential for designing effective oral health strategies. The Child Oral Health Impact Profile (COHIP-SF19) assesses OHRQoL in children but lacks validation in diverse cultural contexts, including Ethiopia. This study aimed to adapt the COHIP-SF 19 to Amharic and evaluate its psychometric properties among schoolchildren in the Amhara region. Methods The original English COHIP-SF 19 was translated into Amharic (COHIP-SF 19) using a standard forward and backward translation procedure, followed by cultural adaptation to ensure the tool’s relevance and accuracy in the Ethiopian context. 400 schoolchildren who were grades 6 to 8th included Internal consistency reliability, test-retest reliability, discriminant validity, convergent validity, and floor and ceiling effects computed to evaluate the Amharic version of COHIP-SF 19. A Mann-Whitney U test was used to compare mean scores of COHIP-SF 19 based on participants’ caries status and self-reported oral health rating. Results Mean age of the schoolchildren was 13.3 ± 0.97 years and 51.5% of them were female. The mean scores for the socio-emotional, oral health, and functional subscales were 29.35 (± 7.765), 13.21 (± 3.99), and 9.99 (± 3.29), respectively. Both the internal consistency (Cronbach’s alpha = 0.90) and test–retest reliability (intra-class correlation coefficient (ICC) of (0.89) were found within an acceptable range. Discriminant validity was confirmed via the Mann-Whitney U test, showing that children without dental caries had significantly higher COHIP-SF19 scores (Z = -13.81, p < 0.001). Overall, the Amharic version COHIP-SF19 showed an acceptable level of equivalence to the original version. Conclusion In this study, the COHIP-SF19 Amharic version demonstrated adequate cultural validity and reliability for assessing Oral Health-Related Quality of Life in Ethiopian schoolchildren. It is suitable for use in clinical practice, service evaluation, and research to measure OHRQoL among Ethiopian schoolchildren.